(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Hyperlipidemia describes a condition in which a patient has high levels of lipids (LDL & triglycerides), low levels of HDL in their blood. Hyperlipidemia is a significant risk factor for heart disease and stroke and it often coexists in patients who are obese. It is very common, especially in modern developed countries. It is also increasing around the world. The prevalence of hypercholesterolemia is around 79% in Indian population. It is said that every 1% reduction in lipid levels, the risk of heart diseases reduces by 2.5%. People with untreated hyperlipidemia are twice likely to develop coronary artery disease (CAD) as those with cholesterol levels in the normal range. This can lead to clogged arteries, which can trigger heart attack, stroke or other serious problems. In Ayurvedic literature, hyperlipidemia is considered as Medo Vriddhi, where Meda refers to one of the Dhatus and Vriddhi means increase. In Medo Vriddhi or Medo roga bahu adaddha medas circulates in the body. In Ayurveda, hyperlipidemia can be called as Atisthaulya or Medo roga and Prameha. All these occur due to Guru snigdha ahara sevana which leads to Ama uttaptti and the Ama produces the Agni vikriti. This Ama goes directly to the Medo dhatu and gets combined with Kapha at tissue level and cause increase in Medo dhatu.